2023
DOI: 10.3346/jkms.2023.38.e40
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends and Characteristics of Adult Patients in Emergency Department Related to Suicide Attempt or Self-Harm in Korea, 2016–2020

Abstract: Background The implementation of an effective suicide prevention program requires the identification and monitoring of subpopulations with elevated risks for suicide in consideration of demographic characteristics, to facilitate the development of tailored countermeasures for tackling the risk factors of suicide. We examined the annual trends in emergency department (ED) visits for suicide attempts (SAs) or self-harm and investigated the sex- and age-specific characteristics of individuals who vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…In particular, it was observed that the incidence rate per 100,000 population among women increased significantly, especially after the COVID-19 outbreak. Previous research on self-harm patients in Korea demonstrated similar sexual discrepancies in self-harm patients to this study and also revealed that young women have made a growing contribution to increasing self-harm rates among females over the last few years [11,12]. However, sex-specific in-hospital mortality rates exhibited a reverse trend to the incidence rate.…”
Section: Discussionsupporting
confidence: 83%
“…In particular, it was observed that the incidence rate per 100,000 population among women increased significantly, especially after the COVID-19 outbreak. Previous research on self-harm patients in Korea demonstrated similar sexual discrepancies in self-harm patients to this study and also revealed that young women have made a growing contribution to increasing self-harm rates among females over the last few years [11,12]. However, sex-specific in-hospital mortality rates exhibited a reverse trend to the incidence rate.…”
Section: Discussionsupporting
confidence: 83%
“…This suggests that suicidal behavior among men is more lethal than among women ( 42 ). As noted by Lee et al ., there is a need to develop tailored suicide prevention initiatives based on age and gender ( 43 ). Suicide or self-harm are pivotal social concerns that depend on several factors.…”
Section: Discussionmentioning
confidence: 99%